The Dualistic Nature of Christ: A Comparison Study of Herman Bavinck And Ellen White Thoughts - Christar Arstilo Rumbay (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2020)
Abstract: Christology has been a subject of wide discussion due the very heart of Christianity lays on this doctrine. Further, it relates directly to some core identity of believers such as soteriology, trinity and atonement. The intention of this treatise is to delve and offer alternative perspectives that may contribute to the discourse. However, the natures of Christ are one of the high attentions given. The divinity and humanity attributes participate consistently in dialogues. Herman Bavinck, a Dutch reformed background, and Ellen White with American Adventist tradition share insights to the topic. This essay goes to compare their thought in order to see the contribution that could be offered.   Keywords: divinity-humanity, Christology, Herman Bavinck, Ellen White  Abstrak: Kristologi menjadi topik pembahasan luas karena menjadi dasar doktrin kekristenan. Lebih jauh, Kristologi memiliki korelasi langsung dengan inti keyakinan seperti soteriology, trinitas dan penebusan. Tujuan dari tulisan ini adalah untuk menggali dan menawarkan perspektif alternative yang dapat berkontribusi pada diskursus ini. Kodrat dari Kristus adalah atensi utama dalam pembahasan ini. Karakter ketuhanan dan kemanusiaan diulas secara konsisten. Herman Bavinck, latar belakang tradisi reformasi Belanda, dan Ellen White dengan tradisi Adventist di Amerika merefleksikan pengetahuan mengenai topik ini. Artikel ini mencoba memberikan perbandingan dengan tujuan untuk melihat kontribusi yang dapat ditawarkan.